A Web-Based Simulation Game for Teaching Supply Chain Management. (September 2020) - Chuang, Ming-Ling
Supply chain management (SCM) is a complex business discipline because it combines the concepts of forecasting, inventory management, logistics and distribution, vertical and horizontal integration, and global issues. This complexity creates a challenge when teaching the concepts to both undergraduate and graduate students. A web-based computer simulation can be very useful in helping students to grasp the difficult concepts. It helps students to think systematically and logically as they progress through scenarios with uncertainties and complexity. This article provides detailed implementation protocols for using a web-based SCM game including game descriptions, classroom pedagogy, and simulation assessment. Recommendations are also provided based on the instructor's experience.